ممرات المشاة (الرصيف)‎ في المدينة اليمنية بين الإمكانات و الطموح : دراسة حالة مدينة المكاد- اليمن: السقاف، ياسر خالد بكير، زكريا عبد الرحمن - السقاف، ياسر خالد بكير، زكريا عبد الرحمن (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN This research is studying and analyzing the footpath in Yemen's city as one of the important elements within the city. and its importance comes in the context of the various functions performed by users, in addition to its association with the level of civilization of the members of the community. It is an architectural and an important element in dealing with different cultural levels exist within any community. Because there are no clear studies and standards with many clear attacks upon the footpaths and its areas. This study with a field survey was done in Mukalla city (study area) to recognized the footpath kinds in the city and the public and private footpath filling and the users behaviors with this footpath kinds that we can defined the footpath problems that suffered Mukalla city. The situation of the city was studied refers to the common and clear scientific standards from several sides. The study concludes to a set of findings and recommendations, which can be followed in order to improve the situation of the sidewalks in Yemeni cities